Andy Jarvis from Kew Gardens, London - Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
CIAT's Andy Jarvis provides our first-ever video diary, from his visit to London's Royal Botanic Gardens at Kew. Andy is in the UK to plan the early stages of an ambitious project to document, collect and conserve endangered wild plan species around the world.